Transformasi Digital Dalam Manajemen Sumber Daya Manusia: Strategi Peningkatan Kinerja Karyawan Di Era Industri 4.0 - Sahnas Asalpiah Zamaludin (AMMA : Jurnal Pengabdian Masyarakat, 2026)
Digital transformation has become a global phenomenon that changes various aspects of organizational life, including human resource management. The rapid development of digital technology in the Industry 4.0 era encourages organizations to integrate technology into HR activities to improve efficiency, effectiveness, and productivity. This study aims to analyze the role of digital transformation in human resource management and its impact on employee performance. This research employs a qualitative approach using a literature review method. The findings reveal that the implementation of technologies such as Human Resource Information Systems (HRIS), e-recruitment, e-learning, digital performance management, and people analytics can improve HR management quality and employee performance. Digital transformation also supports data-driven decision-making and employee engagement. However, challenges such as resistance to change, limited digital competencies, technology investment costs, and data security risks remain obstacles. Therefore, organizations need comprehensive strategies through training, digital culture development, and technological infrastructure enhancement to ensure successful digital transformation.